Embodied Identity in a Literary Work: Analyzing Women's Body Representation in the Film ‘Imperfect’ through Simone de Beauvoir's Lens - Permatasari, Marsella Putri; Amilia, Fitri; Suaedi, Hasan; Dzarna, Dzarna (Journal of Language and Literature Studies, 2024)
As a prominent medium within the realm of literary works, film serves as a popular medium with a strong influence on public perceptions of various phenomena and issues, particularly as media act as conduits for societal control in the modern era. This study aims to explore the representation of women's bodies in the film Imperfect by Ernest Prakasa through the lens of Simone de Beauvoir's existentialist feminist theory. The research focuses on two main aspects: societal beauty standards for women's bodies and the female protagonist's resistance to these standards. Imperfect portrays the social pressures women face to conform to narrow, patriarchal standards of beauty, such as a slim figure and fair skin. The study employs a descriptive qualitative method, with data collection techniques including observation and note-taking. Observation is conducted through attentive viewing of the film, while note-taking involves documenting relevant dialogues and scenes. Data analysis is carried out systematically in several stages: transcribing key scenes, identifying and classifying scenes that reflect beauty standards and the concept of "the Other," and conducting in-depth analysis of the gathered data. The findings indicate that the film often positions women as "the Other," or as objects judged by external standards. Through its main character, the film also presents a form of resistance to these standards, underscoring the importance of self-acceptance and the freedom to define beauty independently. This study hopes to contribute to the discourse on existentialist feminism and highlight relevant issues regarding social pressures on women’s bodies in Indonesian popular culture.